Long-term clinical results of MR-guided stereotactic body radiotherapy of liver metastases - Weykamp, Fabian; Hoegen-Saßmannshausen, Philipp; Regnery, Sebastian; Katsigiannopulos, Efthimios; Renkamp, Claudia Katharina; Uzun-Lang, Kristin; König, Laila; Sandrini, Elisabetta; Meixner, Eva; Rippke, Carolin; Buchele, Carolin; Liermann, Jakob; et al. (Cancers, 2023)
Magnetic-resonance (MR)-guided stereotactic body radiotherapy (SBRT) allows for ablative, non-invasive treatment of liver metastases. However, long-term clinical outcome data are missing.